Gamified Quizzes as Media to Enhance Students’ English Reading Comprehension Skills - Fitri Damanik; yenita br sembiring; Valentina Br Karo; Ira Maria Frans Lumbanbatu; Merry Susanty Br Tarigan (Teaching English and Language Learning English Journal, 2026)
This study examines how gamified quizzes can support junior high school students in improving their English reading comprehension. Using a qualitative approach, the research gathered rich insights from 25 students through interviews, focus group discussions, classroom observations, and weekly reflective journals. Throughout the lessons, students engaged with reading activities that included interactive game elements such as points,timers, and leaderboards. The findings show that these gamified quizzes helped students understand texts more effectively, especially when identifying main ideas, recognizing supporting details, and making inferences. Students reported that the instant feedback and engaging format made them more willing to reread passages and reflect on their answers. The study also found a noticeable increase in students’ motivation. Many who previously felt bored or uninterested in reading became more enthusiastic when tasks were presented as challenges. In addition, students demonstrated stronger critical-thinking habits, such as analyzing information more carefully and discussing different interpretations with their peers. Overall, the study suggests that gamified quizzes not only make reading activities more enjoyable but also encourage deeper thinking and more consistent engagement. These results highlight the potential of gamification as a meaningful addition to traditional reading instruction.